PENGARUH PROFESIONALISME GURU DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII - Muinah Muinah (Universitas Muhammadiyah Kotabumi, 2017)
This research aimed at knowing the influence of teacher’s profesionalisme and learning motivation and both of them toward students’ mathematic learning achievement at the seventh grade. The research population was all of the seventh grade of SMP Islam Terpadu Insan Robbani Kotabumi consisting of 3 class and 105 students. The sampel was a class wich consist of 35 studen that taken by using cluster random sampling and gotten VIIB as sampel class. Data collecting technique was done using a questionnaire for the teacher’s profesionalisme level and learning motivation data, while a test was used to measure the data of students’ mathematic learning achievement. Furthermore, the items analysis was done using validity, reliability, and discrimination power. Meanwhile, Hypotheses test was done using product moment and regression formula. The reserach resultshows that: 1) Teacher’s profesionalisme gives positive and significant influence on students’ mathematic learning achievement. 2) The learning motivation alsogives positive and significant influence on their mathematic learning achievement. 3) Teacher’s profesionalisme and learning motivation give positive and significant influence on students’ mathematic learning achievement.